Earthquake surface ruptures on the altiplano and geomorphological evidence of normal faulting in the December 2016 (Mw 6.1) Parina earthquake, Peru. (March 2021) - Aguirre, Enoch; Benavente, Carlos; Audin, Laurence; Wimpenny, Sam; Baize, Stéphane; Rosell, Lorena; Delgado, Fabrizio; García, Briant; Palomino, Anderson
Abstract: The 2016 Mw 6.1 Parina earthquake ruptured a shallow-crustal normal fault within the high Andes of south Peru. We use high-resolution DEMs and field mapping of the surface ruptures generated by the earthquake, in combination with co-seismic and post-seismic InSAR measurements, to investigate how different features of the geomorphology at Parina are generated by the earthquake cycle on the Parina Fault. We systematically mapped 12 km of NW-SE trending surface ruptures with up to ~27 cm vertical displacement and ~25 cm tensional opening along strike, separated by a gap with no observable surface ruptures. Co- and post-seismic InSAR measurements require slip below this gap in surface ruptures, implying that surface offsets observed in paleoseismic trenches may not necessarily be representative of slip at seismogenic depths, and will typically yield an underestimate of paleo-earthquake magnitudes. The surface ruptures developed along 10–20 m high cumulative scarps cutting through late Quaternary fluvio-glacial deposits and bedrock. The 2016 Parina earthquake did not rupture the full length of the late Quaternary scarps, implying that the Parina Fault does not slip in characteristic, repeat earthquakes. At Parina, and across most of the Peruvian Altiplano, normal faults are most-easily identified from recent scarps cutting late Quaternary moraine crests. In regions where there are no recently-deposited moraines, faults are difficult to identify and lack time constraints to quantify rates of fault slip . For this reason, current fault maps may underestimate the seismic hazard in the Altiplano . Highlights: We present a survey of surface ruptures following a Mw 6.1 earthquake in the Altiplano of Peru. High-resolution DEMs and mapping highlight the co-seismic and long-term geomorphic imprint of the active normal fault system.